Carbon-covered mesoporous silica and its application in Rhodamine B adsorption. Issue 9 (3rd May 2018) - Nascimento, R. C. S.; Silva, A. O. S.; Meili, L.
ABSTRACT: Modified versions of MCM-41 and SBA-15 were obtained from sucrose by carbon deposition. The ability of the resulting materials, MCM-41 CC and SBA-15 CC, to remove Rhodamine B from aqueous solutions was evaluated. TG/DTG, XRD, Nitrogen Adsorption (BET), and SEM were used to characterize the materials. Adsorption was investigated by finite bath studies. To characterize the adsorption behavior and mechanism, kinetics and equilibrium were assessed. MCM-41 CC provided the best adsorption results: adsorptive capacity of 11.91 mg of dye/g of material and 91.95% w/v dye removal ( C 0  = 50 mg L −1 ). The sucrose particles interacted well, to result in improved area and micropore volume. Hence, carbon deposition can afford materials with increased adsorptive capacity depending on the sieve employed during their preparation.